Effect of nickel doping on magnetic and dielectric properties of orthorhombic calcium ferrite nanoparticles - R. UmashankaraRaja; Y.S. Vidya; H.C. Manjunatha; M. Priyanka; R. Munirathnam; K.M. Rajashekara; S. Manjunatha; E. Krishnakanth (Green Energy and Resources, 2024)
Nickel (10∼50 mol%) doped calcium ferrite nanoparticles (NPs) are synthesized by the solution combustion method using lemon juice extract as a reducing agent, followed by calcination at 500°C. The calcined samples are characterized with different techniques. The Bragg reflections of Nickel doping confirm the formation of a single orthorhombic calcium ferrite phase. The crystallite size is estimated using both Scherrer's and the W-H plot method. The surface morphology consists of irregular size and shaped agglomerated NPs along with pores and voids. A blueshift and a broad absorption spectrum is observed with an increase in the direct energy band gap. The direct energy band gap estimated from Wood and Tauc's relationship was found to be 2.91∼2.97 eV with an increase in dopant concentration. The magnetic analysis provided values for saturation magnetization (Ms), remanence (Mr), and coercivity (Hc), while dielectric studies demonstrated a dielectric constant of 2.81, 2.14, and 1.67 with increasing dopant concentration. The variation of dielectric properties of the sample as a function of frequency in the range 0.1∼20 MHz has been studied at room temperature. The dielectric properties of CaFe2O4: Ni (1∼9 mol%) NPs clearly indicate that there is a more pronounced dispersion at lower frequencies, gradually reaching saturation as the frequency increases. The dielectric loss was found to decrease from 4.62, 3.22, and 2.32 with an increase in Ni2+ substitution (10, 30, and 50 mol%) respectively. These results indicate the suitability of these samples for applications in memory devices and high-frequency applications.